Health Promotion Behavior Through "Isi Piringku" for Pregnant Women, Babies, and Toddler in the Working Area of the Banjarsengon Community Health Center as a Stunting Prevention Action: Promosi Perilaku Upaya Kesehatan Melalui "Isi Piringku" Pada Ibu Hamil, Bayi, dan Balita di Wilayah Kerja Puskesmas Banjarsengon Sebagai Upaya Pencegahan Stunting (AgroNurse Kesehatan : Jurnal Pengabdian Masyarakat, 2023)
Stunting is a chronic nutritional problem that is one of Indonesia's leading public health problems. This community service activity aimed to improve knowledge and skills in enhancing the nutritional status of pregnant women and mothers with babies and toddlers so that the community can implement balanced nutrition guidelines to reduce the risk of stunting. This community service method includes three stages: preparation for implementing activities, health education, and the evaluation stage. This activity indicated that almost half of the people (44.12%) who participated in this activity have adequate knowledge about the contents of "isi piringku". Meanwhile, after health education, most participants (76.67%) had adequate knowledge, and all participants demonstrated grown knowledge. This community service showed a significant difference in knowledge scores about balanced nutrition guidelines "isi piringku" before and after implementing health education (p-value 0.000). This community service reveals the importance of promoting health behavior in terms of health education in the community. Therefore, it is necessary to regularly implement health education on balanced nutrition guidelines to prevent nutritional problems, especially stunting, in the community.